Recent development of Civil Procedural Law in Thailand: the Class Action and the Legal Execution - Wisuttisak, Pornchai (Brawijaya Law Journal, 2018)
The paper aims to study on the overview of civil procedural law in Thailand with emphasis on the recent amendment regarding to class action and legal execution. The civil procedural law in Thailand, known as Procedural Use of Civil and Commercial Codes Act 1937 was passed in 1938 as to formulate the trail, execution of judgment, and appeal in civil and commercial codes. The civil procedural law in Thailand became a vital legal rules governing a proper civil trial and judgments. This Thailand Civil Procedural Law was recently amended on the provisions of class action and the efficiency of the legal execution. It is argued that such amandment create vital impact to legal practices on civil procedurals in Thailand. The amendment helps to modernize the rules for class action and facilitates the process on legal execution in Thailand. Adopting juridical normative method with statute approach, this paper submitted that civil procedural law should be amended throughfuly and not only partialy to keep up with the rapid changes on civil and commercial cases. To achieve this, more amandments of Procedural Use of Civil and Commercial Codes Act 1937 need to be done.